Law Enforcement against Criminal Action with Fingerprint Evidence - Wilddan Auliya; Jawade Hafidz (Law Development Journal, 2020)
The objectives of this study are 1) To study and analyze law enforcement against the perpetrator of the crime of theft using fingerprint evidence. 2) To analyze the factors that influence law enforcement against the perpetrators of criminal acts of theft. 3) To formulate should be obstacles and solutions in law enforcement against perpetrators of criminal acts of theft with fingerprint evidence in the future. This research method uses empirical juridical research. The results of the study concluded that: 1) Law enforcement against perpetrators of criminal acts of theft with fingerprint evidence uses 2 (two) means, namely: a) Non-penal means are law enforcement against criminal acts using the means non penal includes the use of social facilities to improve certain social conditions, but indirectly affects efforts to prevent crime. b) Penal facility Penal facility is the prevention of crime by using criminal law and for studying fingerprints or often referred to as evidence which is one part of assistive science used by the police in taking and studying fingerprints. 2) The factors that influence law enforcement on the eradication of criminal acts of theft consist of internal and external factors. Internal factors consist of social inequality, economic inequality, injustice. 3) Constraints and solutions in law enforcement against perpetrators of criminal acts of theft with fingerprint evidence a) the obstacles faced are legal aspects and aspects of investigators b) Solutions in law enforcement against perpetrators of criminal acts of theft with fingerprint evidence require a role/action Indonesian Police in law enforcement, especially in handling criminal acts of theft with fingerprint evidence (dactyloscopy), it can be seen that the police action in dealing with criminal acts of theft in the future is besides maintaining its procedures (Permanent Program), namely chain patrols, early detection, handling of TKP that were attacked by the Police, Polwiltabes and Central Java Regional Police/as well as case titles until the case is revealed.